ChemInform Abstract: Gold(I)‐Catalyzed Angle Strain Controlled Strategy to Furopyran Derivatives from Propargyl Vinyl Ethers: Insight into the Regioselectivity of Cycloisomerization. Issue 27 (16th June 2016) - Jin, Shengfei; Jiang, Chongguo; Peng, Xiaoshi; Shan, Chunhui; Cui, Shanshan; Niu, Yuanyuan; Liu, Yang; Lan, Yu; Liu, Yongxiang; Cheng, Maosheng
Abstract: The utility of this method is demonstrated in the synthesis of the mycotoxin isopatulin (IV).